Laser Output Performance and Temporal Quality Enhancement at the J-KAREN-P Petawatt Laser Facility - Hiromitsu Kiriyama; Yasuhiro Miyasaka; Akira Kon; Mamiko Nishiuchi; Akito Sagisaka; Hajime Sasao; Alexander S. Pirozhkov; Yuji Fukuda; Koichi Ogura; Kotaro Kondo; Nobuhiko Nakanii; Yuji Mashiba; et al. (Photonics, 2023)
We described the output performance and temporal quality enhancement of the J-KAREN-P petawatt laser facility. After wavefront correction using a deformable mirror, focusing with an f/1.3 off-axis parabolic mirror delivered a peak intensity of 1022 W/cm2 at 0.3 PW power levels. Technologies to improve the temporal contrast were investigated and tested. The origins of pre-pulses generated by post-pulses were identified and the elimination of most pre-pulses by removal of the post-pulses with wedged optics was achieved. A cascaded femtosecond optical parametric amplifier based on the utilization of the idler pulse rather than the signal pulse was developed for the complete elimination of the remaining pre-pulses. The orders of magnitude enhancement of the pedestal before the main pulse were obtained by using a higher surface quality of the convex mirror in the Öffner stretcher. A single plasma mirror was installed in the J-KAREN-P laser beam line for further contrast improvement of three orders of magnitude. The above developments indicate, although it has not been directly measured, the contrast can be as high as approximately 1015 up to 40 ps before the main pulse. We also showed an overview of the digital transformation (DX) of the system, enabling remote and automated operation of the J-KAREN-P laser facility.